Are personnel with a past history of mental disorders disproportionately vulnerable to the effects of deployment-related trauma? A cross-sectional study of Canadian military personnel - Beliveau, Peter J; Sampasa-Kanyinga, Hugues; Colman, Ian; Zamorski, Mark A (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Past mental disorders predict future disorders, both in the presence and absence of trauma exposure. However, it is not clear whether those with past mental disorders are disproportionately vulnerable to the negative effects of a given level of trauma. Methods The data source was the 2013 Canadian Forces Mental Health Survey (CFMHS), of which 1820 respondents had deployed only once in their military careers—all in support of the mission in Afghanistan. The primary outcomes were past 12-month depression and past 12-month PTSD. Multivariate logistic regression was performed for each outcome variable, looking primarily for differences in the marginal effect of deployment-related trauma in those with and without a pre-deployment history of each disorder. Results A history of each pre-deployment disorder did indeed interact with deployment-related trauma with respect to the corresponding past 12-month disorder. In addition, pre-deployment history of depression and of PTSD interacted with each other, though only for the outcome of past 12-month PTSD. The average marginal effect of deployment-related trauma on past 12-month PTSD was highest in those with a pre-deployment history of depression in the absence of a pre-deployment history of PTSD. This group was twice as vulnerable to post-deployment PTSD relative to those without a pre-deployment history of both disorders and four times as vulnerable to post-deployment PTSD relative to those with a pre-deployment history of both disorders. No significant differences were seen in the marginal effects of trauma on past 12-month depression in the presence or absence of a pre-deployment history of that disorder. Conclusion There is modest differential vulnerability to past 12-month PTSD as a function of deployment-related trauma in those who had a pre-deployment history of PTSD or depression when compared to those who did and did not have a pre-deployment history of one or both disorders.